PENGEMBANGAN MODUL IPA TERPADU BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS, MINAT, DAN HASIL BELAJAR SISWA PADA MATERI FOTOSINTESIS DI KELAS VIII SMP NEGERI 9 JAYAPURA - KALEMBEN, SIMON; RUMAHORBO, BASA; SIALLAGAN, JOHNSON (Jurnal Ilmu Pendidikan Indonesia, 2018)
This research is a research and development that aims to know to create anÂ Â integrated IPA module, the feasibility of integrated IPA module, the improvement of science process skill, the interest and studentâ€™s learning process by using integratedÂ IPA module, the advantages and disadvantages using integrated IPA module. This research conducted in class VIII A of SMP Negeri 9 Jayapura with 40 students. The result shows that : 1) The improvement of integrated IPA module based on inquiry on photosynthesis material is started with defining phase, module planning, draft module design, and development 2) The feasibility of integrated IPA module from validator 99.40 % with very decent category, IPA teachers got 90% with very good category, and the result of try out in small scale got 84.16% 3) The improvement of students process skill by using integrated IPA module got 78.68% with skilled category 4) The improvement of students interest in using Â got 96.25% with very high category 5) The improvement of student learning result students got average 46 in average pretest, and it increase be 70.50 in posttest and n- Gain got 0.45 with middle category 6) Â Integrated IPA module can improve the process skill, students interest and learning result. Key words: Module, Integrated Science, Guided Inquiry, Science Processs skills, Interests, Learning Outcomes